THE PRACTICE OF USING DIGITAL TECHNOLOGIES IN EDUCATION (European Journal of Economics, Finance and Business Development, 2024)
The development of the world economy will be influenced by cognitive factors (from the Latin word “cognition” — “knowledge”, “thinking”) and the economy of economy, production based on nanotechnology and biotechnology. This leads to a sharp increase in the amount of information required to develop and make management decisions in the economy.